2021
DOI: 10.1523/jneurosci.0367-21.2021
|View full text |Cite
|
Sign up to set email alerts
|

Broadband Dynamics Rather than Frequency-Specific Rhythms Underlie Prediction Error in the Primate Auditory Cortex

Abstract: Detection of statistical irregularities, measured as a prediction error response, is fundamental to the perceptual monitoring of the environment. We studied whether prediction error response is associated with neural oscillations or asynchronous broadband activity. Electrocorticography was conducted in three male monkeys, who passively listened to the auditory roving oddball stimuli. Local field potentials (LFPs) recorded over the auditory cortex underwent spectral principal component analysis, which decoupled… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 141 publications
(202 reference statements)
2
35
0
Order By: Relevance
“…However, our findings appear incompatible with earlier studies that found γ -synchronization to be positively related to prediction errors ( Arnal et al., 2011 ; Bastos et al., 2020 ; Chao et al., 2018 ; Bauer et al., 2014 ). Notably, these studies used temporal predictability, whereas the present study used spatial predictability, and the generalization of our findings to temporal predictability remains to be demonstrated (see Vinck and Bosman, 2016 ; Peter et al., 2019 ; Canales-Johnson et al., 2021 for further discussion). We further note that there are different flavors of predictive coding theories ( Rao and Ballard, 1999 ; Friston, 2008 ; Mumford, 1992 ; Keller and Mrsic-Flogel, 2018 ; de Lange et al., 2018 ; Heeger, 2017 ; Singer, 2021 ).…”
Section: Discussionmentioning
confidence: 69%
“…However, our findings appear incompatible with earlier studies that found γ -synchronization to be positively related to prediction errors ( Arnal et al., 2011 ; Bastos et al., 2020 ; Chao et al., 2018 ; Bauer et al., 2014 ). Notably, these studies used temporal predictability, whereas the present study used spatial predictability, and the generalization of our findings to temporal predictability remains to be demonstrated (see Vinck and Bosman, 2016 ; Peter et al., 2019 ; Canales-Johnson et al., 2021 for further discussion). We further note that there are different flavors of predictive coding theories ( Rao and Ballard, 1999 ; Friston, 2008 ; Mumford, 1992 ; Keller and Mrsic-Flogel, 2018 ; de Lange et al., 2018 ; Heeger, 2017 ; Singer, 2021 ).…”
Section: Discussionmentioning
confidence: 69%
“…beta and gamma). However, the spectrum of mesoscopic electrophysiological signals (e.g., LFP, EEG) also contains aperiodic or 'arrhythmic' [64][65][66] that have been related to the integration of underlying synaptic currents 67 . Problematically, the standard approach of analyzing periodic power or phase synchronization (e.g., wPLI) through band-pass filtering confounds both periodic and aperiodic activity 68 .…”
Section: Discussionmentioning
confidence: 99%
“…This study did not find evidence for narrow-band gamma oscillations, and found that the increase in LFP gamma power for deviant tones was driven by increases in broad-band power. Additional analyses based on multiscale multifractal analyses suggest that the increase in broad-band energy reflects an underlying aperiodic process (Canales-Johnson et al, 2021a).…”
Section: The Gamma Rhythm In Predictive Processingmentioning
confidence: 99%
“…This structure reflects, at least in part, low-pass filtering of synaptic currents in the intracellular space (Pesaran et al, 2018;Einevoll et al, 2013). Rhythms need to be detected against this aperiodic 1/ f a background, which requires the detection of narrow-band peaks (Hermes et al, 2015;Canales-Johnson et al, 2021a;Miller et al, 2009;Donoghue et al, 2020). The observation of synchronized spiking and the identification of a generative circuit is necessary to establish that this peak reflects a locally generated rhythm (Buzsáki et al, 2012;Buzsáki and Schomburg, 2015).…”
Section: The Gamma Rhythm In Predictive Processingmentioning
confidence: 99%
See 1 more Smart Citation